FAK PROTAC Inhibits Ovarian Tumor Growth and Metastasis by Disrupting Kinase Dependent and Independent Pathways - Huo, Xueyun; Zhang, Wenjing; Zhao, Guannan; Chen, Zhenwen; Dong, Peixin; Watari, Hidemichi; Narayanan, Ramesh; Tillmanns, Todd D.; Pfeffer, Lawrence M.; Yue, Junming (Frontiers in Oncology, 2022)
Focal adhesion kinase (FAK) is highly expressed in a variety of human cancers and is a target for cancer therapy. Since FAK kinase inhibitors only block the kinase activity of FAK, they are not highly effective in clinical trials. FAK also functions as a scaffold protein in a kinase-independent pathway. To effectively target FAK, it is required to block both FAK kinase-dependent and FAK-independent pathways. Thus, we tested a new generation drug FAK PROTAC for ovarian cancer therapy, which blocks both kinase and scaffold activity. We tested the efficacy of FAK PROTAC and its parent kinase inhibitor (VS-6063) in ovarian cancer cell lines in vitro by performing cell functional assays including cell proliferation, migration, invasion. We also tested in vivo activity in orthotopic ovarian cancer mouse models. In addition, we assessed whether FAK PROTAC disrupts kinase-dependent and kinase-independent pathways. We demonstrated that FAK PROTAC is highly effective as compared to its parent FAK kinase inhibitor VS-6063 in inhibiting cell proliferation, survival, migration, and invasion. FAK PROTAC not only inhibits the FAK kinase activity but also FAK scaffold function by disrupting the interaction between FAK and its interaction protein ASAP1. We further showed that FAK PROTAC effectively inhibits ovarian tumor growth and metastasis. Taken together, FAK PROTAC inhibits both FAK kinase activity and its scaffold protein activity by disrupting the interaction between FAK and ASAP1 and is highly effective in inhibiting ovarian tumor growth and metastasis.